Concrete Hollow Block with Reused Glass - Yuhani Jamian; Munirah Abd Rahim (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
Concrete is being used a lot in construction. As urbanization accelerates globally, the demand for sustainable construction materials is becoming increasingly critical. Traditional concrete, a staple in the construction industry, is known for its environmental impact due to high energy consumption in production and the extensive use of natural resources. In response to these concerns, researchers and industry practitioners are exploring innovative approaches to enhance the sustainability of construction materials. One promising area of investigation is the incorporation of recycled materials into concrete mixtures. In this study, we aimed to determine the level of glass replacement resulting in optimal compressive strength. The objectives of this study are to produce a concrete hollow block with reused glass and to find out whether the reused glass can be used as partial replacement for aggregates. Three concrete samples were tested at 7, 14 and 28 days for glass replacement proportions of 10%, 15% and 20%. Based on its maximum load at failure, 10% of reused glass substitution is applicable for interior wall. The hollow concrete produced by using 10% of reused glass with sized 320cmx180cmx180cm.